Can negotiations at the World Health Organization lead to a just framework for the prevention, preparedness and response to pandemics as global public goods? - Viviana Mu\~noz Tellez (South Centre, 2022)
This paper advances that WHO Member States, having agreed to the objectives of advancing equity and solidarity for future pandemic prevention, preparedness and response, now must operationalize these. The paper offers suggestions for the ongoing WHO processes of: 1) review of recommendations under examination by the Working Group on Strengthening WHO Preparedness and Response to Health Emergencies, 2) consideration of potential amendments to the International Health Regulations (IHR) 2005, and 3) elaboration of a draft text for an international instrument on pandemic preparedness and response.
Keywords: 300; Access to Medicines; Coronavirus; COVID-19; Equity; Flexibilities; Global Public Good; Health; Intellectual Property; International Health Regulations (IHR); Pandemic; Pandemic Preparedness and Response; Pandemic Treaty; Patent; Research and Development (R&D); Solidarity; TRIPS; TRIPS Waiver; Vaccines; Working Group on Strengthening WHO Preparedness and Response to Health Emergencies (WGPR); World Health Organization (WHO)